Analisis Klaster Kemiskinan 38 Provinsi Indonesia Berdasarkan Pengaruh Sumber Daya Manusia, Infrastruktur, Ekonomi dengan DBSCAN - Riamto, Mohammad Shodiq Wahyu; Donoriyanto, Dwi Sukma (Jurnal Algoritma, 2025)
Poverty is a multidimensional issue that describes the condition of lack of opportunity, low ability, low level of security, and low capacity. In Indonesia, poverty is still a major problem that has not been resolved. The condition of an archipelagic country is a challenge in achieving equitable prosperity. Therefore, this study aims to map 38 provinces in Indonesia according to the results of DBSCAN clustering based on the analysis of the influence of human resource quality, infrastructure availability, and economic growth. Mapping of poor and non-poor provinces in Indonesia was carried out using the Density-Based Spatial Clustering of Applications with Noise (dbscan) cluster method which utilizes secondary data from BPS in the education, health, employment, etc. sectors. The results of the study showed that regional poverty mapping was divided into two clusters, namely 17 poor cluster provinces and 21 non-poor cluster provinces with a cluster evaluation value of 0.645 (fair cluster). Based on the analysis of the influence of poverty factors, 17 poor provinces are influenced by the high percentage of the population who have not attended school until the age of 15 years which is caused by the lack of educational infrastructure and the mindset of local communities who are less concerned about education and low infrastructure can hinder the economic growth of GRDP, resulting in inflation being difficult to control. Based on these conditions, the government has an important role in providing infrastructure in various sectors and the need for socialization of higher education to parents and students to ensure a decent life in the long term. Thus, it can be concluded that poverty in Indonesia can be resolved if the community cares about higher education and the government provides adequate and quality infrastructure in various sectors. It is hoped that the first point of the 2030 SDGs target can be completed.